Speculative Wests : popular representations of a region and genre - Johnson, Michael K. (Michael Kyle), 1963- (Postwestern horizons., 2023)
""Speculative Wests" investigates representations of the American West in terms of both region and genre, looking at speculative westerns (involving science fiction, fantasy, and horror) as well as at speculative texts that feature western settings"--